Genome-wide analysis of urogenital and respiratory multidrug-resistant Haemophilus parainfluenzae. (1st April 2021) - Sierra, Yanik; González-Díaz, Aida; Carrera-Salinas, Anna; Berbel, Dàmaris; Vázquez-Sánchez, Daniel Antonio; Tubau, Fe; Cubero, Meritxell; Garmendia, Junkal; Càmara, Jordi; Ayats, Josefina; Ardanuy, Carmen; Marti, Sara
Abstract: Objectives: To characterize the mechanisms of antimicrobial resistance and the prevalence of the polysaccharide capsule among urogenital and respiratory Haemophilus parainfluenzae isolates. Methods: Antimicrobial susceptibility was tested by microdilution. Fifty-five MDR strains were subjected to WGS and were phylogenetically compared with all the available H. parainfluenzae genomes from the NCBI database. The identification of the capsular bexA gene was performed by PCR in 266 non-MDR strains. Results: In 31 of the 42 ampicillin-resistant strains, bla TEM-1 located within Tn 3 was identified. β-Lactamase-negative cefuroxime-resistant strains ( n  = 12) presented PBP3 substitutions. The catS gene ( n  = 14), the tet (M) - MEGA element ( n  = 18) and FolA substitutions (I95L and F154V/S) ( n  = 41) were associated with resistance to chloramphenicol, tetracycline plus macrolides, and co-trimoxazole, respectively. Thirty-seven isolates had a Tn 10 harbouring tet (B)/(C)/(D)/(R) genes with ( n  = 15) or without ( n  = 22) catA2 . Putative transposons (Tn 7076–Tn7079 ), including aminoglycoside and co-trimoxazole resistance genes, were identified in 10 strains (18.2%). These transposons were integrated into three new integrative and conjugative elements (ICEs), which also included the resistance-associated transposons Tn 3 and Tn 10 . The capsular operon was found only in the urogenital isolates (18/154, 11.7%), but no phylogenetic clustering was observed. The capsular operons identified were similar to those of Haemophilus influenzae serotype c and Haemophilus sputorum type 2. Conclusions: The identification of ICEs with up to three resistance-associated transposons suggests that these transferable elements play an important role in the acquisition of multidrug resistance in H. parainfluenzae . Moreover, the presence of polysaccharide capsules in some of these urogenital isolates is a cause for concern.